Most textbooks (also this blog) cover the fact that ridge regression,

$$ \hat y = \hat \beta X; \\ \hat \beta = \underset{\beta}{\text{argmin}}\ \ \frac{(y-\beta X)^T(y-\beta X)}{\sigma^2} + \lambda \|\beta\|_2^2; $$

can be interpreted as a MAP estimate of a Bayesian model with $N(0, \tau)$ priors on the $\beta$ parameters, where

$$ \lambda = \frac{\sigma^2}{\tau^2} $$ What is the equivalent Bayesian interpretation of logistic ridge regression?

$$ \hat y = logit^{-1}(\hat \beta X); \\ \hat \beta = \underset{\beta}{\text{argmin}}\ \ -y\ log(\hat y) - (1-y)\ log(1 - \hat y) + \lambda \|\beta\|_2^2; $$

I'm looking for this both out of theoretical interest, and because I would like to use stochastic gradient descent to estimate MAP logistic regression parameters in a context (JavaScript) where I don't have access to any specialised solvers.


2 Answers 2


As a preliminary note, I see that your equations seem to be dealing with the case where we only have a single explanatory variable and a single data point (and no intercept term). I will generalise this to look at the general case where you observe $n$ data points, so that the log-likelihood function is a sum over these $n$ observations. (I will use only one explanatory variable, as in your question.) For a logistic regression of this kind you have the observable values $Y_i|\mathbf{x}_i \sim \text{Bern}(\mu_i)$ with true mean values:

$$\mu_i \equiv \mathbb{E}(Y_i|\mathbf{x}_i) = \text{logistic}(\boldsymbol{\beta}^\text{T} \mathbf{x}) = \frac{e^{\boldsymbol{\beta}^\text{T} \mathbf{x}}}{1+e^{\boldsymbol{\beta}^\text{T} \mathbf{x}}}.$$

The log-likelihood function is given by:

$$\begin{align} \ell(\mathbf{y}|\mathbf{x},\boldsymbol{\beta}) &= \sum_{i=1}^n \log \text{Bern}(y_i|\mu_i) \\[6pt] &= \sum_{i=1}^n y_i \log (\mu_i) + \sum_{i=1}^n (1-y_i) \log (1-\mu_i) \\[6pt] &= \sum_{i=1}^n y_i \log (\mu_i) + \sum_{i=1}^n (1-y_i) \log (1-\mu_i) \\[6pt] &= \sum_{i=1}^n y_i \log(\boldsymbol{\beta}^\text{T} \mathbf{x}) - \sum_{i=1}^n y_i \log(1+e^{\boldsymbol{\beta}^\text{T} \mathbf{x}}) - (1-y_i) \log(1+e^{\boldsymbol{\beta}^\text{T} \mathbf{x}}) \\[6pt] &= \sum_{i=1}^n y_i \log(\boldsymbol{\beta}^\text{T} \mathbf{x}) - \sum_{i=1}^n \log(1+e^{\boldsymbol{\beta}^\text{T} \mathbf{x}}). \\[6pt] \end{align}$$

Logistic ridge regression operates by using an estimation method that imposes a penalty on the parameter $\boldsymbol{\beta}$ that is proportionate to its squared norm. (Note that you have stated this slightly incorrectly in your question.) It estimates the parameter $\boldsymbol{\beta} = (\beta_1,...,\beta_K)$ via the optimisation problem:

$$\begin{align} \hat{\boldsymbol{\beta}}_\text{Ridge} &= \underset{\boldsymbol{\beta} \in \mathbb{R}^K}{\text{argmax}} \ \ \ \ \ell(\mathbf{y}|\mathbf{x},\boldsymbol{\beta}) - \lambda ||\boldsymbol{\beta}||^2. \\[6pt] \end{align}$$

Since the log-posterior is the sum of the log-likelihood and log-prior, the MAP estimator is:

$$\begin{align} \hat{\boldsymbol{\beta}}_\text{MAP} &= \underset{\boldsymbol{\beta} \in \mathbb{R}^K}{\text{argmax}} \ \ \ \ \ell(\mathbf{y}|\mathbf{x},\boldsymbol{\beta}) + \log \pi(\boldsymbol{\beta}). \\[6pt] \end{align}$$

We obtain the result $\hat{\boldsymbol{\beta}}_\text{Ridge} = \hat{\boldsymbol{\beta}}_\text{MAP}$ by using the prior kernel $\pi(\boldsymbol{\beta}) \propto \exp(- \lambda ||\boldsymbol{\beta}||^2)$ so that $\log \pi (\boldsymbol{\beta}) = - \lambda ||\boldsymbol{\beta}||^2 + \text{const}$ in the above equation. Integrating to find the constant of integration gives the prior distribution:

$$\pi(\boldsymbol{\beta}) = \prod_k \mathcal{N} \bigg( \beta_k \bigg| 0, \frac{1}{2\lambda} \bigg).$$

Thus, we see that ridge logistic regression is equivalent to MAP estimation if a priori the individual $\beta_k$ parameters are IID normal random variables with zero mean. The variance parameter for this normal distribution is a one-to-one mapping of the "penalty" hyperparameter in the ridge logistic regression --- a larger penalty in the ridge regression corresponds to a smaller variance for the prior.

(Note: For a related question showing LASSO and ridge regression framed in Bayesian terms see here.)


To look for equivalence one should compare the form of,

$$\hat{\beta} = \underset{\beta}{\text{argmin}} -y\log(\hat{y}) - (1-y)\log(1-\hat{y}) + \lambda||\beta||_2^2,$$

with the posterior distribution whilst keeping a general expression for the prior. The posterior distribution has form, $$\pi(\beta|x) \propto \pi(\beta)L(\beta;x).$$ Where $\pi(\beta)$ is the prior and $L(\beta;x)$ is the likelihood. Noting that $\beta$ is $p\times1$ and that $x$ represents the data where $x_i$ is one observation and would be $p\times1$. In logistic regression the model for the data is Bernoulli (more generally Binomial). So, $$y_i|\beta,x_i \sim Bernoulli(p_i)$$ where $p_i = \frac{\exp\{\beta^Tx_i\}}{1 + \exp\{\beta^Tx_i\}}.$ Let $f(\cdot)$ be the density function, then the posterior for $\beta$ becomes

\begin{align*} \pi(\beta|x)&\propto\pi(\beta)\prod_{i=1}^{n}f(x_i|\beta) \\ &= \pi(\beta)\prod_{i=1}^{n}p_i^{y_i}(1-p_i)^{1-y_i}. \end{align*} The maximum-a-posterior (MAP) of $\beta$ is the mode of its posterior distribution and since $\log$ is monotone, $$\hat{\beta}_{MAP} = \underset{\beta}{\text{argmax}}\pi(\beta|x) = \underset{\beta}{\text{argmax}}\log\pi(\beta|x).$$ So taking, $$\log\pi(\beta|x) \propto \log\pi(\beta) + \sum_{i=1}^n\big\{y_i\log p_i + (1-y_i)\log(1-p_i)\big\}$$ and noting that $\hat{\beta}_{MAP} = \underset{\beta}{\text{argmax}}\log\pi(\beta|x) = \underset{\beta}{\text{argmin}}\big\{-\log\pi(\beta|x)\big\}$ we can see that, \begin{align*} \log\pi(\beta) &\propto - \lambda||\beta||_2^2 \\ \Rightarrow \pi(\beta) &\propto \exp\{-\lambda||\beta||_2^2\}. \end{align*} This can be seen as taking independent normal priors with mean zero and variance $\frac{1}{2\lambda}$, $$\beta_j \sim N\left(0,\frac{1}{2\lambda}\right) \ \ j=1,\dots,p.$$

  • $\begingroup$ Thanks. Do you have any idea of a reference for the conclusion, specifically that the penalty $\lambda$ matches the prior precision $\frac{1}{\sigma^2}$? $\endgroup$
    – Eoin
    Commented Jul 6, 2020 at 17:55
  • $\begingroup$ Sure. This comes from comparing the form of $\exp\{-\lambda\beta_j\}$ with that of a normal density and then manipulating the constants so that the forms match. In this case we are only interested in $\beta$ and because it is a proportional relationship we can multiply by any constant. Apologies I had previously made a mistake with $\frac{1}{\lambda}$, this has been fixed to $\frac{1}{2\lambda}$. $\endgroup$
    – ztkpat001
    Commented Jul 6, 2020 at 19:32

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.